El cuerpo abusado y el imaginario médico y legal en la comprobación del delito - Rosalina Estrada Urroz (Centre de Recherches sur les Mondes Américains, 2010)
In the practice of the medical examination in the cases of rape, the opinion of the expert exceeds his function, he does not only inspect the genitalia of the victim and the blows that would verify the sexual assault; the sinuosities of the body, the look of the victim and the hygiene are objects of evaluation. A wide range of epithets is revealed this way; the imaginary and the subjectivities expressed by means of the words go beyond the technical description. The inspection of the fact faces a set of difficulties; since it is not only necessarily that the penis penetrates the vagina, but the presence of the semen of the aggressor is also obligatory. Blood and semen appear as the pair that surrounds the lack of modesty, both fluids are considered by different criteria, the first one offers doubts about its origin; the presence of the second one is necessary to prove the crime. The future of the victim is in the hands of the experts and the possibilities of defense are constructed by the social strategies that help recover the loss of honor. In the case of women who have a marital life, it is rare that the expert is called to examine the victim, in this way it is evident that virginity is the only situation that deserves to be considered for "the repair of honor".